SIGNIFICANCE OF PEDIATRIC PALLIATIVE CARE FOR PARENTS OF CHILDS WITH END-OF-LIFE ISSUES IN INDIA (International Journal of Food and Nutritional Sciences, 2022)
Based on their data analysis and discoveries in this field, researchers have reached conclusions concerning PC. Following the conclusion the government has made no meaningful move to promote the application of the ayurvedic system to the field of PC. Modern medicine practitioners are not required to have any specialized certifications in order to provide care to the terminally sick. It is capable of sensing the void and lacuna connected with the current global medical system in order to provide care to the patient. It is feasible if sufficient education and facilities are supplied. Address the concerns of patients who are unable to be assisted by the medications that are now available. Internal medicine is the practice of internal medicine that is advocated by modern medicine.